Migratory Movements and Home Ranges of Geographically Distinct Wintering Populations of a Soaring Bird - Ryo Ogawa; J. Brian Davis; D. Tommy King; L. Wes Burger; Bronson K. Strickland; Marsha A. Sovada; Guiming Wang; Fred L. Cunningham (Diversity, 2022)
Migratory soaring birds exhibit spatiotemporal variation in their circannual movements. Nevertheless, it remains uncertain how different winter environments affect the circannual movement patterns of migratory soaring birds. Here, we investigated annual movement strategies of American white pelicans Pelecanus erythrorhynchos (hereafter, pelican) from two geographically distinct wintering grounds in the Southern and Northern Gulf of Mexico (GOM). We hypothesized that hourly movement distance and home range size of a soaring bird would differ between different geographic regions because of different thermals and wind conditions and resource availability. We calculated average and maximum hourly movement distances and seasonal home ranges of GPS-tracking pelicans. We then evaluated the effects of hour of the day, seasons, two wintering regions in the Southern and Northern GOM, human footprint index, and relative pelican abundance from Christmas Bird Count data on pelican hourly movement distances and seasonal home ranges using linear mixed models and generalized linear mixed models. American white pelicans moved at greatest hourly distance near 1200 h at breeding grounds and during spring and autumn migrations. Both wintering populations in the Northern and Southern GOM exhibited similar hourly movement distances and seasonal home ranges at the shared breeding grounds and during spring and autumn migrations. However, pelicans wintering in the Southern GOM showed shorter hourly movement distances and smaller seasonal home ranges than those in the Northern GOM. Hourly movement distances and home ranges of pelicans increased with increasing human footprint index. Winter hourly movements and home ranges of pelicans differed between the Northern and Southern GOM; however, the winter difference in pelican movements did not carry over to the shared breeding grounds during summers. Therefore, exogenous factors may be the primary drivers to shape the flying patterns of migratory soaring birds.